2021
DOI: 10.1093/alcalc/agab004
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Balloon Analogue Risk Task (BART) in Alcohol Research

Abstract: Risk-taking propensity has been crucial to the investigation of alcohol use and consequences. One measure, the balloon analogue risk task (BART), has been used consistently over the past two decades. However, it is unclear how this measure is related to alcohol outcomes. This paper systematically reviews the literature on the BART and alcohol outcomes. First, direct associations between the BART and alcohol use are reviewed including correlations, group comparisons, the BART’s prediction of alcohol outcomes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 103 publications
0
23
0
Order By: Relevance
“…The data analysis did not reveal any statistically significant differences, and small effect sizes among groups from the decision-making tasks. In consideration of the evidence demonstrated by the literature on each type of task (2,6,8,15), these results were not expected; however, we are aware that we had a small sample size with insufficient power to detect such a difference (see Table 2).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The data analysis did not reveal any statistically significant differences, and small effect sizes among groups from the decision-making tasks. In consideration of the evidence demonstrated by the literature on each type of task (2,6,8,15), these results were not expected; however, we are aware that we had a small sample size with insufficient power to detect such a difference (see Table 2).…”
Section: Discussionmentioning
confidence: 75%
“…For example, one of the most affected cognitive abilities is decisionmaking (1,2). Recent studies have demonstrated that substance abusers who are in treatment (alcohol, cocaine, heroin, tobacco, and methamphetamine) exhibit extreme values of choosing small immediate rewards over large delay rewards (i.e., steeply delay discounting) (3)(4)(5), and risk-taking behaviors (6)(7)(8). Nevertheless, it remains unclear whether risk-taking behaviors are associated with impulsivity (i.e., steeply delay discounting).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By implementing suboptimal designs in previous studies, the approximation of individual risk-taking behavior may have been biased or noisy (see also Kılıç et al, 2020;Yakobi and Danckert, 2021). Comprehensive studies tend to indicate discrepancies across patterns of results involving the BART (Bishara et al, 2009;Purcell et al, 2017;De Groot and Thurik, 2018;Canning et al, 2022). For example, Maner and colleagues (2007) reported effects of anxiety on risk-taking, while a later study did not find such association (Buelow and Barnhart, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying paradigm is reasonably practical and straightforward, the BART in its standard design entails unsolved criticalities that may hinder the usefulness of the collected data. Previous works discussed putative issues of the BART, including the censoring of information, the confusion of risk with the expected value, a poor distinguishing between uncertainty and risk, and the ambiguity in the definition of adaptive versus maladaptive behavior (Schonberg et al, 2011;De Groot and Thurik, 2018;De Groot, 2020;Canning et al, 2022). While these concerns are relevant, a significant source of inaccuracies in the BART is the unsafe interaction between two stochastic processes.…”
Section: Introductionmentioning
confidence: 99%